2015
DOI: 10.1155/2015/638526
|View full text |Cite
|
Sign up to set email alerts
|

Targeting Insulin-Like Growth Factor Binding Protein-3 Signaling in Triple-Negative Breast Cancer

Abstract: Insulin-like growth factor binding protein-3 (IGFBP-3) is a key regulatory molecule of the IGF axis and can function in a tissue-specific way as both a tumor suppressor and promoter. Triple-negative breast cancer (TNBC) has high tumor expression of IGFBP-3 associated with markers of poor prognosis and, although accounting for 15–20% of all breast cancers, is responsible for disproportionate rates of morbidity and mortality. Because they lack estrogen and progesterone receptors and overexpression of HER2, TNBC … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
37
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(38 citation statements)
references
References 82 publications
1
37
0
Order By: Relevance
“…IGFBP-3 is also known to regulate cell survival independently of the IGF/IGF-IR axis [39][40][41][42] . Expression of IGFBP-3 is reduced 43 in lung cancer and associated with poor diagnosis in patients with stage I NSCLC [44][45][46][47][48] . There is an inverse relationship between plasma or serum levels of the protein and lung cancer risk 34,39,49 .…”
mentioning
confidence: 99%
“…IGFBP-3 is also known to regulate cell survival independently of the IGF/IGF-IR axis [39][40][41][42] . Expression of IGFBP-3 is reduced 43 in lung cancer and associated with poor diagnosis in patients with stage I NSCLC [44][45][46][47][48] . There is an inverse relationship between plasma or serum levels of the protein and lung cancer risk 34,39,49 .…”
mentioning
confidence: 99%
“…1 It was first identified as a binding partner of IGFs for stabilizing the IGFs in blood and an inhibitor of IGF-1 receptor (IGF1R) signaling by blocking IGF binding to receptors in tissues. 2 Overexpression of IGFBP3 is found in renal clear cell carcinomas, 23 head and neck squamous cancers, 15 pancreatic ductal adenocarcinomas, 29 and aggressive breast cancers, 17 and its expression is associated with poor patient outcome. IGFBP3 functions as a tumor promoter by enhancing cell growth through increasing sphingosine kinase-1 (SphK1) expression and sphingosine-1 phosphate (S1P) formation, which transactivates epidermal growth factor receptor (EGFR) or IGF1R signaling pathways.…”
mentioning
confidence: 99%
“…Insulin-like growth factor binding protein-3 (IGFBP-3) is a key regulatory molecule in the IGF axis and functions in a tissue-specific way as both a tumor suppressor and promoter [11]. Zhao et al [12] reported that ESCC patients carrying the IGFBP-3 rs2854744 GG or GC genotype have a significantly better response to CRT and longer OS than those with the CC genotype.…”
Section: Positive Biomarkers In Blood Examinationmentioning
confidence: 99%